The meaning of providing caring to obese patients to a group of nurses - Emilly Souza Marques; Géssyca Cavalcante de Melo; Regina Maria dos Santos (Universidade Federal de Goias, 2014)
This qualitative study was performed with six nurses of a public hospital, with the objective to describe their view of the meaning of providing care to obese patients. Interviews were conducted using a semi-structured script. The data were organized under themes extracted from the subjects' statements, after being thoroughly read. Symbolic Interactionism was adopted to interpret the findings. The results from the analysis were organized under the following themes: Being obese is excessive, it is not healthy; Providing care to the obese is a structural issue; Obese patients are troublesome, they require care, no big deal; Providing care to the obese requires teamwork. The grasped meanings can interfere in the care provided. The nurses, however, recognize the need to work as a team to deliver comprehensive care. Making positive changes to the meanings found in this study is possible, thus, contributing to providing prejudice-free nursing care to obese patients. Descriptors: Obesity; Nursing Care; Hospital Care.